Comparative characteristics of liberal and restrictive fluid resuscitation in multiple trauma. - D. A. Krishtafor; O. M. Klygunenko (Medičnì Perspektivi)
The aim of the study was a comparative analysis of components in liberal and restrictive fluid resuscitation and their effectiveness. 90 patients with multiple trauma divided into two groups, depending on the fluid resuscitation type (liberal or restrictive) were studied. Infusion components in 1st day, intraoperative blood loss, ICU and hospital stay length, number of complications and lethality were investigated. Restrictive fluid resuscitation type in multiple trauma was characterized by a decrease of total infusion volume in ml/kg in 1st day by 34.8%, including crystalloids – by 34.2%, colloids – by 71.4% with a constant volume of FFP and erythrocytes. Balanced crystalloid solutions were used more often, and solutions of potassium and magnesium asparaginate and glucose, high-molecular HES and dextranes were not used at all. Blood components were introduced earlier. Volume of intraoperative blood loss decreased by 34.0%, the frequency of complications – by 1.6 times, the mortality rate – by 2 times.